Branch and bound method for multiobjective pairing selection - Kariwala, Vinay; Cao, Yi (Elsevier Science B.V., Amsterdam., 2010)
Most of the available methods for selection of input-output pairings for decentralized control require evaluation of all alternatives to find the optimal pairings. As the number of alternatives grows rapidly with process dimensions, pairing selection through an exhaustive search can be computationally forbidding for large-scale processes. Furthermore, the different criteria can be conflicting necessitating pairing selection in a multiobjective optimization framework. In this paper, an efficient branch and bound (BAB) method for multiobjective pairing selection is proposed. The proposed BAB method is illustrated through a biobjective pairing problem using selection criteria involving the relative gain array and the mu-interaction measure. The computational efficiency of the proposed method is demonstrated by using randomly generated matrices and the large-scale case study of cross-direction control. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Computer-aided control system design Decentralized control Global optimization Large-scale systems Multiobjective optimizations Relative gain array Structured singular value decentralized control systems optimization algorithms framework